Pembuatan Sabun dari Minyak Jelantah sebagai Upaya Pengelolaan Limbah Rumah Tangga Di Desa Jatiroyo melalui kegiatan Kuliah Kerja Nyata - Muhammad Mirza Al Rosiif; Muhammad Hibatul Ghaniyyu; Maria Maharani; Mohammad Rizky Fauzy; Nalea Ananda Gayatri; Febra Udha Eka Listiyana; Ahmad Fauzan; Sabrinna Intan; Mutia Mutia; Ayu Puspitasari Apriliani; Putri Permatasari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Waste cooking oil is a common household waste that is often improperly disposed of, leading to environmental pollution and potential health risks. The increasing consumption of cooking oil contributes to the growing volume of waste oil, while public awareness regarding proper management remains limited. Improper disposal practices, such as pouring waste oil into drainage systems or soil, can degrade water quality, disrupt aquatic ecosystems, and increase pollution indicators such as Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). This study aimed to improve community knowledge and skills in managing waste cooking oil through environmentally friendly soap-making training. The program was conducted by students of the Community Service Program (KKN) of Universitas Sebelas Maret through counseling and hands-on training for members of the Family Welfare Movement (PKK) in Jatiroyo Village. A participatory and practice-based approach (learning by doing) was applied, incorporating zero waste principles (reduce, reuse, recycle). The program involved 45 participants and included stages such as environmental education, demonstration, and direct practice of soap production. The results indicated a significant improvement in participants’ understanding of environmental and health impacts, with approximately 90% of participants able to independently produce soap after the training. The program also increased environmental awareness and practical skills, showing strong potential as a sustainable waste management solution and an opportunity for community-based economic empowerment..